Participation and inclusion in extracurricular physical activities: an ethnographic study alongside children with disabilities - Westwood, Katherine (The University of Edinburgh, 2022)
The aim of this thesis is to explore how children with disabilities experience their participation in extracurricular physical activities. The thesis closes a gap in literature by contributing an in-depth year-long collection of lived experiences of extracurricular physical activities which was developed alongside children with disabilities in London Ontario. Knowledge was created alongside 10 children with disabilities by utilizing an ethnographic methodology. Multi-site ethnography was adapted for each participant’s needs and communication methods. The methodology contributes to literature by a creative adaptation to interviewing children and having a flexible approach to methods which was chosen by the children themselves. The thesis answers what inclusion looks like as a lived experience in extracurricular physical activity environments, along with how adults and children create opportunities and constraints for children’s recognized participation. The analysis identified that there is a gap in understanding between literature of participation and inclusion and children with disabilities knowledge and preferences. Additionally, findings indicate that children with disabilities that communicate non-verbally experience inclusion differently than children with disabilities who communicate verbally. The knowledge created builds on literature of various attitudes and beliefs of children with disabilities by providing a further in-depth connection to lived experience, participation and inclusion opportunities. The thesis concludes by emphasizing a flexible approach to creating knowledge alongside children with disabilities, and more specifically advocating for more inclusion of children who communicate non-verbally in research. The thesis suggests an emphasis for continuous communication to understand changing perceptions of participation and inclusion from the perspectives of children themselves and how it is shaped by the surrounding environment and interactions.